Exceptional electrochemical performance of nitrogen-doped porous carbon for lithium storage. (February 2015) - Wang, Heng-guo; Wang, Yinghui; Li, Yanhui; Wan, Yuchun; Duan, Qian
Abstract: Crumpled nitrogen-doped porous carbon sheets are successfully fabricated via chemical activation of polypyrrole-functionalized graphene sheets with KOH (APGs). The obtained APGs with nitrogen doping, high surface area, porous and crumpled structure exhibit exceptional electrochemical performances as the electrode material for LIBs, including a superhigh reversible specific capacity of 1516.2 mAh g −1, excellent cycling stability over 10, 000 cycles, and good rate capability (133.2 mAh g −1 even at a very high current density of 40 A g −1 ). The chemical activation synthesis strategy might open new avenues for the design of high-performance carbon-based anode materials.